2018
DOI: 10.1111/jfpp.13638
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soluble soybean polysaccharide and tragacanth gum based edible coating to improve the quality of fresh-cut apple slices

Abstract: The effects of soluble soybean polysaccharides (SSPS) (1, 2, 3% wt/vol) and Tragacanth gum (0.1, 0.3, 0.5 wt/vol) containing 0.5% calcium chloride and 2% ascorbic acid on physicochemical quality of fresh cut apple slices as edible coatings have been investigated for 12 days at 4 °C. Increase SSPS concentration was associated with greater maintenance of titrated acidity. Slices treated with 3% SSPS and 0.5% Tragacanth gum had the highest and lowest tissue firmness, respectively, on day's 12. The sample with 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In order to evaluate the firmness of the samples, the penetration test was performed using a TA‐XT Plus texture analyzer (Stable Micro Systems) equipped with a 25‐N load cell and a cylindrical puncture probe, 6 mm in diameter, at a constant speed of 10 mm/min (Jafari et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the firmness of the samples, the penetration test was performed using a TA‐XT Plus texture analyzer (Stable Micro Systems) equipped with a 25‐N load cell and a cylindrical puncture probe, 6 mm in diameter, at a constant speed of 10 mm/min (Jafari et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…A Minolta colorimeter CR‐400 (Konica Minolta, Inc) was used to assess the color of the samples based on the CIELab color space. Total color difference (∆E) was used to examine the color changes in the samples (Jafari et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…During storage, the untreated apple wedges lost firmness faster than the coated fruits. CMC and A. vera coatings, in combination with anti-browning chemicals, increased the quality of preserved apple (Jafari et al, 2018) [33] . Moreira et al studied the addition of apple fiber, combined with ascorbic acid was found to preserved antioxidant activity for at least one week of storage.…”
Section: Effects Of Edible Coating On Fresh-cut Fruits 31 Applementioning
confidence: 99%
“…Edible and natural coatings are applied to food to act as a barrier to the environment, hence decreasing microbes, water, and oxygen exposure (Omidi‐Mirzaei et al, 2020; Phothiset & Charoenrein, 2007). In addition, it has been reported that polysaccharides coating such as pectin or gums on food can keep moisture, while aiding in surface water removal and avoiding firm texture in the end food product after drying (Jafari et al, 2018; Lyu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%